Modern vaccines and coronavirus infections - Yu. A. Belikova; Yu. V. Samsonov; E. V. Abakushina (Исследования и практика в медицине, 2020)
Vaccines represent an outstanding success story in modern medicine and are responsible for a huge reduction in morbidity and mortality worldwide. It is clear that improvements are necessary to enable the development of successful vaccines against some difficult pathogens, including human immunodeficiency virus and hepatitis C virus. This review is on recent advances in the development of new generation vaccines, as well as those developed using earlier time-tested technologies: live attenuated vaccines, inactivated vaccines, recombinant vaccines, subunit vaccines, virus-like particle-based vaccines, synthetic peptide vaccines, DNA vaccines and mRNA vaccines. However, many infections are still not preventable with the currently available vaccines and they represent a major cause of mortality worldwide — for example, severe acute respiratory syndrome coronavirus, middle east respiratory syndrome coronavirus and severe acute respiratory syndrome coronavirus 2 that causes coronavirus disease 2019 — COVID-19. As no effective treatment against COVID-19 is currently available, the best action is to develop vaccines to prevent the infection. The majority of candidate vaccines aim to induce neutralizing antibodies against the SARS-CoV-2. Multiple platforms areunder development. Some potential vaccine candidates have progressed to phase I and II clinical trials. In Russia, a vector vaccine based on adenovirus DNA, which has the SARS-CoV-2 virus gene embedded in it, is undergoing clinical trials.